MiniCD4 microbicide prevents HIV infection of human mucosal explants and vaginal transmission of SHIV(162P3) in cynomolgus macaques. - Nathalie Dereuddre-Bosquet; Laurence Morellato-Castillo; Joachim Brouwers; Patrick Augustijns; Kawthar Bouchemal; Gilles Ponchel; Oscar H P Ramos; Carolina Herrera; Martha Stefanidou; Robin Shattock; Leo Heyndrickx; Guido Vanham; et al. (PLoS Pathogens)
In complement to an effective vaccine, development of potent anti-HIV microbicides remains an important priority. We have previously shown that the miniCD4 M48U1, a functional mimetic of sCD4 presented on a 27 amino-acid stable scaffold, inhibits a broad range of HIV-1 isolates at sub-nanomolar concentrations in cellular models. Here, we report that M48U1 inhibits efficiently HIV-1(Ba-L) in human mucosal explants of cervical and colorectal tissues. In vivo efficacy of M48U1 was evaluated in nonhuman primate (NHP) model of mucosal challenge with SHIV(162P3) after assessing pharmacokinetics and pharmacodynamics of a miniCD4 gel formulation in sexually matured female cynomolgus macaques. Among 12 females, half were treated with hydroxyethylcellulose-based gel (control), the other half received the same gel containing 3 mg/g of M48U1, one hour before vaginal route challenge with 10 AID(50) of SHIV(162P3). All control animals were infected with a peak plasma viral load of 10(5)-10(6) viral RNA (vRNA) copies per mL. In animals treated with miniCD4, 5 out of 6 were fully protected from acquisition of infection, as assessed by qRT-PCR for vRNA detection in plasma, qPCR for viral DNA detection in PBMC and lymph node cells. The only infected animal in this group had a delayed peak of viremia of one week. These results demonstrate that M48U1 miniCD4 acts in vivo as a potent entry inhibitor, which may be considered in microbicide developments.